2000
DOI: 10.1111/j.1572-0241.2000.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fractures in celiac disease patients: a cross-sectional, case-control study

Abstract: This study has demonstrated that patients with celiac disease had a high prevalence of bone fractures in the peripheral skeleton. Most of these events occurred before diagnosis or while patients were noncompliant with gluten-containing diet. Our results suggest that early diagnosis and effective treatment of celiac disease were the most relevant measures to protect patients from the risk of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(93 citation statements)
references
References 16 publications
1
86
0
6
Order By: Relevance
“…One study has reported an increased risk of peripheral fractures in those with celiac disease. However, most fractures were recorded prior to diagnosis or in those noncompliant with their gluten-free diet [14]. Another study challenged this finding by reporting no increased risk of fractures before or after the diagnosis, yet verification of the diagnosis of celiac disease was low (78%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…One study has reported an increased risk of peripheral fractures in those with celiac disease. However, most fractures were recorded prior to diagnosis or in those noncompliant with their gluten-free diet [14]. Another study challenged this finding by reporting no increased risk of fractures before or after the diagnosis, yet verification of the diagnosis of celiac disease was low (78%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional, case control study (25) of 165 Argentinian adults with malabsorption detected fractures in 25% of patients with symptomatic celiac disease but only 8% of those with functional gastrointestinal disorders. Radial and vertebral fractures were most common; three-fourths of the fractures in celiac patients occurred before the age of 50.…”
Section: The Case For Screening-michael Freemarkmentioning
confidence: 99%
“…Moreover, CD associates with metabolic bone disease. The frequency of low bone mineral density (BMD) among coeliac patients varies widely between different studies due to differences in diagnostic criteria, geographical distribution and patient selection (12)(13)(14). The presence of significant malabsorption leads to a more severe bone loss in CD (15), although BMD is lower in asymptomatic patients compared to healthy subjects, as well (16).…”
Section: K Lorinczy Et Al Rev Esp Enferm Dig (Madrid)mentioning
confidence: 99%